Political party families and student social rights - Krzysztof Czarnecki (Journal of European Social Policy, 2022)
The article conceptualizes student funding systems in order to investigate their ideological and political underpinnings. Using different long-term measures of cumulative power of four-party families and their combinations, and the newly created Student Support and Fees Dataset, it shows that the variety of student social rights in 32 high-income democracies in 2015 can be linked to past partisan politics. Decommodification, understood as making higher education study unconditional on labour income of students and their families, was positively associated with the rule of pro-welfare parties and negatively with the rule of Conservative parties, in the preceding two decades. Individualization, that is the state support for student transition to independent adulthood, was positively associated with the rule of left-wing parties. This, however, applies only to their long-term impact in older democracies and is to a large extent conditional on a country's wealth. Third, social rights distribution characterized by a low degree of targeting and large recipiency rate was similarly related to the Left rule, while the Conservatives ruling in the last two decades contributed to increasing inequalities in student social rights.
Keywords: 320; student funding; social rights; government ideology; party families; comparative social policy